Art of Caring Model for Emergency Care Patients and Professionals - Elmqvist, Carina (Nursing philosophy, 2025)
The Art of Caring model is developed from a general structure of the flow in the encounter between the injured patients and the different professionals within emergency care, in turn founded on four phenomenological essences, which encompass the experiences of patients, next of kin, and various professionals during the encounter at the scene of an accident and at the emergency department. The Art of Caring model represents a philosophical and theoretical rethinking of an ethical approach. It draws upon the works of the Danish philosopher Løgstrup, the French philosopher Levinas as well as selected aspects of Merleau Ponty. The Art of Caring model is illustrated by coppersmith and artist Michaela Ivarsdotter, further developed and reflected upon with Anna Bratt, a psychologist working according to the compassion-focused tradition. The model is made to disclose and visualise the Art of Caring and facilitate reflections on achieving a win-win situation for both patients and different professionals within emergency care. Healthcare involves a variety of professions, and for the benefit of the patient, we must recognise the significance of professionals taking on the advocacy role from a caring science perspective, which includes the unique and shared experiences of the lifeworld. This is a challenge within the context of demanding efficiency and time pressure in emergency care. To address this, a concrete action plan for ethical reflections is needed to find a balance between giving and receiving, essential for healthcare professionals to avoid compassion fatigue. In the context of ethical competence and the challenges faced by different healthcare professionals within emergency care, the Art of Caring model could be used for ethical reflections, as an approach to achieve a balance between patient advocacy, ethical considerations, and effective emergency care delivery. Achieving this goal will lead to better patient outcomes and a more supportive work environment for the entire emergency care team.